Analisis Risiko Pelaksanaan Pembangunan Jembatan Waborobo - Batu Popi Kota Bau-Bau - Yoyo Yoyo; Hanafi Ashad; Watono Watono (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Risk management is a process carried out in order to respond to a risk that occurs or is likely to occur through a process of risk identification and analysis. The implementation of the construction of the Waborobo Bridge - Batu Popi, Bau-Bau City, experienced delays during its implementation. From the identification results, it was found that 35 risks occurred and the results of the risk level assessment using the Probability Impact Matris (PIM) method showed that there were 9 risk variables with dominant categories, namely: High rainfall intensity, high water discharge or flooding, changes in design and technical work due to adjustments. with field conditions, changes in work implementation schedules, poor access to the project site, difficulty accessing heavy equipment to the project site, damage to equipment or heavy equipment during work, delays in material delivery from suppliers and fatigue due to the large amount of work being done overtime. Risk mitigation carried out is planning the sequence of activities well in accordance with weather records, using pumps to remove stagnant water or mud from the project site, waiting for a decision from the owner regarding the design plan that will be used, rescheduling and intensively handling workers and work in progress. experiencing schedule changes, planning access or departure or mobility, looking for alternative tools or replacing with new tools, ordering materials before starting work, making material ordering schedules before starting work, providing optimal supervision, so that materials do not arrive late at the project location, providing additional vitamins for workers on site when doing overtime and increasing the number of working hours (overtime). Keywords: Risk Management, Development, Bridges